Associations Between Penetration Cognitions, Genital Pain, and Sexual Well-Being in Women with Provoked Vestibulodynia. Issue 3 (1st March 2016) - Anderson, Alexandra B.; Rosen, Natalie O.; Price, Lisa; Bergeron, Sophie
ABSTRACT: Introduction: Provoked vestibulodynia (PVD) is a common vulvovaginal pain condition that negatively impacts women's psychological and sexual well-being. Controlled studies have found that women with PVD report greater negative and less positive cognitions about penetration; however, associations between these types of cognitions and women's pain and sexual well-being remain unknown. Further, researchers have yet to examine how interpersonal variables such as sexual communication may impact the association between women's penetration cognitions and PVD outcomes. Aim: We examined associations between vaginal penetration cognitions and sexual satisfaction, sexual function, and pain in women with PVD, as well as the moderating role of sexual communication. Methods: Seventy-seven women (M age = 28.32, SD = 6.19) diagnosed with PVD completed the catastrophic and pain cognitions and positive cognitions subscales of the Vaginal Penetration Cognition Questionnaire, as well as the Dyadic Sexual Communication Scale. Participants also completed measures of sexual satisfaction, sexual function, and pain. Main Outcome Measures: Dependent measures were the (i) Global Measure of Sexual Satisfaction Scale; (ii) Female Sexual Function Index; and (iii) Present Pain Intensity scale of the McGill Pain Questionnaire, with reference to pain during vaginal intercourse. Results: Women's lower catastrophic and pain cognitions, higher positive cognitions, and higher sexual communication were each uniquely associated with higher sexual satisfaction and sexual function. Lower catastrophic and pain cognitions also were associated with women's lower pain. For women who reported higher sexual communication, as positive cognitions increased, there was a significantly greater decrease in pain intensity during intercourse compared to women who reported lower levels of sexual communication. Conclusion: Findings may inform cognitive-behavioral interventions aimed at improving the pain and sexual well-being of women with PVD. Targeting the couple's sexual communication and women's penetration cognitions may improve women's sexual adjustment and reduce pain.